An Accuracy on the Basis of the Principality of Existence - Muhammad Nejati; Mustafa Momeni; Yaser Salari; Farouq Touli (آموزه‌‌های فلسفه اسلامي, 2022)
Mullā Ṣadrā in the issue of principality of existence with the negation of the conceptual part of existence considers the nonconditioned as a source of division to have extensional unity and individual plurality. The truth of existence has collective and expansionary unity and it is the basis of the principality of existence and the subject of philosophy for this reason. He has two different attitudes towards the existence of the positive condition in the discussion of the validity of the nature of his own. The separation of the principality of existence in two meanings is the result of this discussion: In the first sense, the root of external realties and what fills the external world is the existence of the nonconditioned as a source of division, and the nature or the ranges of the truth of the unconditioned of existence are consequently realized. Ṣadrā in the second and final view considers the validity of nature as a mere mentality by rejecting any external distinction of existence and nature and considers the existence of nature as a function of the existence of the soul and its human minds and its mental aspects.